PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN PRICE EARNING RATIO (PER) TERHADAP HARGA SAHAM : STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yanah, Nur Sopi; Dumadi, Dumadi; Ernitawati, Yenny (LP2M Universitas Bina Bangsa, 2025)
This research was conducted with the aim of examining the influence of Good Corporate Governance (GCG) and Price Earning Ratio (PER) on Stock Prices. Good Corporate Governance which is proxied with the Board of Directors, Board of Commissioners, Independent Board of Commissioners, and Audit Committee. This research is quantitative using secondary data. The study population consisted of 47 banking companies listed on the Indonesia Stock Exchange from 2020-2023, with 29 companies taken as a sample over a 4-year period, resulting in a total of 116 sample data. The sample was selected using the purposive sampling technique based on certain criteria. Data collection technique with the documentation method from the company's financial statements. The data analysis method was carried out by multiple linear regression analysis using SPSS 16 for Windows. The results of the study show that partially, only the variable of the board of directors has a significant effect on the stock price. Meanwhile, simultaneously, Good Corporate Governance which is proxied with the board of directors, board of commissioners, independent board of commissioners, audit committee, and Price Earning Ratio has a significant effect on the stock price by 28.5% and while the remaining 71.5% is influenced by other factors that were not studied in this study